The Acupuncture Effect of Zusanli point (ST36) to Decrease the Number of Leukocytes in Mice (Mus musculus) Model of Sepsis Due to Exposure of Cecal Inoculum - Esty Jayanti; Balgis .; Sri Wulandari (Nexus Biomedika, 2015)
Background:The incidence of sepsis in the Dr. Moewardi Hospital at the end 2007 showed a mortality rate of 50.2 % (115 deaths from 229 patient with sepsis). Associated with the sepsis treatment therapy, the use of low-dose corticosteroids in the early stages of sepsis is still debated. WHO suggests that acupuncture can stimulate corticosteroid. The aim of this study was to know the acupuncture effect of Zusanli point ( ST36 ) to decrease the number of leukocytes in mice (Mus musculus) model of sepsis caused by the exposure of cecal inoculum. Methods:This study was an experimental laboratory research with posttest only control group designs. The samples were 28 male mice, divided by simple random sampling into a control group (KK), Sepsis Group 1 (KS1), Sepsis Group 2 (KS2), and Sepsis Group 3 (KS3). Sepsis groups were made by giving cecal inoculum exposure at a dose of 0.1 mg/mouse/day injected intraperitoneally for 7 days. During the 10 days after exposure, no treatment was given to KS1, while KS2 was treated with corticosteroid therapy, and KS3 was given acupuncture therapy. The low dose corticosteroid used was Methyl prednisolone at a dose of 0.05 mg/mice that was injected intraperitoneally 2 times daily. The acupuncture was given at the Zusanli point (ST36) with a duration of 15 minutes. Blood samples were taken at day 24th. The leukocyte count data were analyzed with One Way ANOVA test (p<0.05) and the Bonferroni post hoc test (p>0.005). Results:Sepsis group were successfully made by exposure of cecal inoculum with significance level (p) of 0.000 (p>0.005). Acupuncture of zusanli point (ST36) could reduce leucocyte count in mice (Mus musculus) model of sepsis caused by exposure to cecal inokulum as same as corticosteroid group with significance level (p) 0.000 (p>0.005). Conclusion:Acupuncture of Zusanli point (ST36) can reduce leukocyte count in mice (Mus musculus) model of sepsis caused by exposure to cecal inoculum. Keywords: Acupuncture, Zusanli point (ST36), leukocyte count, Sepsis.